2001
DOI: 10.1039/b101932p
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for the reactions of NO3•, SO4•- and Cl• radicals with formate and acetate esters in aqueous solution

Abstract: Rate constants for the reactions of and with the esters methyl formate, ethyl formate, methyl NO 3 ~, SO 4 ~~Clã cetate and ethyl acetate in aqueous solution have been measured using pulse radiolysis and laser Ñash photolysis. The reactivities of and are compared with and found to be roughly in the NO 3 ~, SO 4 ~~Cl~~OH order The rates of reaction of with the formate esters in the aqueous phase Cl~B ~OH A NO 3 ~B SO 4 ~~. N O 3 ãre about four orders of magnitude faster than their corresponding gas phase reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…45,[58][59][60][61][62] The only explanation of this behaviour is slightly differing electron densities occurring at the CQC double bond due to electron-withdrawing properties of the deprotonated group. Other studies confirm this trend regardless of whether H abstraction, addition or electron transfer reactions of OH, NO 3 or SO 4 À with saturated, unsaturated or aromatic compounds were considered.…”
Section: Resultsmentioning
confidence: 99%
“…45,[58][59][60][61][62] The only explanation of this behaviour is slightly differing electron densities occurring at the CQC double bond due to electron-withdrawing properties of the deprotonated group. Other studies confirm this trend regardless of whether H abstraction, addition or electron transfer reactions of OH, NO 3 or SO 4 À with saturated, unsaturated or aromatic compounds were considered.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that small esters are present in the interstellar space [1]. The significance of ethyl acetate is in its wide use in industry as a solvent, as well as in production of printing ink, glue or paint [2]. Its presence was also detected in the atmosphere of forests in Central Europe due to biogenic sources emissions [3].…”
Section: Introductionmentioning
confidence: 87%
“…22 [2] on ethyl acetate in aqueous phase that is of importance for acid rain chemistry. All these cases prove that not only is radical attack the main mechanism for the ester removal from the atmosphere, but also that the order of the reactivities of ethyl acetate with such species would be as follows: Cl ≈ OH NO 3 ≈ SO − 4 .…”
Section: Absolute Photoabsorption Cross Sections and Atmospheric Photmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate constant for this reaction (1.3 9 10 4 M -1 s -1 ) [17] is 1,000 times lower than that of OH radicals with acetic acid (1.6 9 10 7 M -1 s -1 ). Therefore, in our system, the main reaction involved in acetic acid decomposition is considered to be an OH radical oxidation reaction.…”
Section: Acetic Acid Decompositionmentioning
confidence: 94%